Pengaruh Pertumbuhan Ekonomi dan Pertumbuhan Penduduk Terhadap Pengangguran Terbuka Di Indonesia (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Abstract Ardiansa, 2019. The influence of Economic Growth and Population Growth on the Open Unemployment in Indonesia (Guided by Michael and Andriawan Kustiawan).The purpose of this study was to analyze: (1) the effect of economic growth on open unemployment with the Okun's law approach. (2) the effect of population growth on open unemployment. (3) variables that predominantly influence open unemployment in Indonesia.This research is a quantitative study using secondary data obtained from the Central Kalimantan Provincial Statistics Agency in the form of time series data (2006-2015). Data analysis using multiple linear regression with Cobb-Douglas production function through classic assumption test and SPSS version 20 program.The results show that economic growth has a negative and not significant effect on open unemployment. Population growth has a positive and significant effect on open unemployment. Economic growth is the dominant variable towards open unemployment in Indonesia